Active polymer behavior in two dimensions: A comparative analysis of tangential and push-pull models - Janzen, Giulia; Miranda, Juan Pablo; Martín-Roca, J.; Malgaretti, Paolo; Locatelli, Emanuele; Valeriani, Chantal; Fernandez, D. A.Matoz (Journal of Chemical Physics, 2025)
In this work, we compare the structural and dynamic behavior of active filaments in two dimensions using tangential and push-pull models, including a variant with passive end monomers, to bridge the two frameworks. These models serve as valuable frameworks for understanding self-organization in biological polymers and synthetic materials. At low activity, all models exhibit similar behavior; as activity increases, subtle differences emerge in intermediate regimes, but at high activity, their behaviors converge. Adjusting for differences in mean active force reveals nearly identical behavior across models, even across varying filament configurations and bending rigidities. Our results highlight the importance of force definitions in active polymer simulations and provide insights into phase transitions across varying filament configurations.
CRIS-Team Scopus Importer:2025-04-01